Evaluation of the Outcomes of Entrepreneurship Education Revisited - Kozlinska, Inna (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
This dissertation addresses two major gaps discernible in contemporary entrepreneurship education (EE) research: firstly, the lack of comparative studies on different forms of EE, such as traditional and experiential, which would test the widely accepted assertion that experiential EE is more effective in generating the desired outcomes in learners; secondly, the lack of evidence of how objective expressions of entrepreneurial behaviour in self- or paid employment are dependent upon entrepreneurship-specific competences that can be developed throughout EE. In bridging these gaps, the dissertation proposes and tests the integrative framework for evaluating the outcomes of EE that conceptually relies on Bloom’s taxonomy of educational objectives (Kraiger et al. 1993; Bloom et al. 1964), human capital theory (Becker 1975), and teaching models in entrepreneurship for higher education (Béchard and Grégoire 2007, 2005b). The applied framework overcomes several trending points of concern in the literature on the impact of EE including the over-reliance on models of entrepreneurial intentions, overlooking, among others, the details of EE design and delivery in the evaluations performed. This novel evaluation framework puts forward the triad of cognitive, skill-based and affective outcomes of EE in the domain of education, and the triumvirate objective outcomes: employability, intrapreneurship and private early-stage entrepreneurial activity (EA) in the domain of entrepreneurship. It conceptualises experiential EE through the prism of demand and competence teaching models, while traditional EE is viewed as analogous of a supply model (ibid 2007). This study focuses on two small, open neighbouring post-transition economies: Estonia and Latvia. The analysis applies a mixed methods embedded design by combining multiple case study, cross-sectional and comparative designs. Data were collected from 16 entrepreneurship educators and from 559 final year bachelor students participating in business-related programmes, and recent graduates from these programmes taught at 8 local HEIs (4 per country). Purposive expert and homogeneous sampling were employed, respectively, at the qualitative and quantitative data collection stages that involved face-to-face semi-structured interviews and an online survey. The interview data were used to diagnose the prevailing form of intervention at each HEI. The survey data were used to test the hypotheses. Content analysis by means of data coding was performed to process the qualitative data. The structural equation modelling was applied to estimate cognitive, skill-based and affective outcomes. The analysis of co-variance was used to determine if statistically significant differences exist between predominantly traditional and experiential teaching and their learning outcomes. In addition, various regression models were run to estimate the association between learning outcomes and objective outcomes as well as between experiential EE and objective outcomes. The findings of the study question the common assumptions mentioned earlier, having brought partial support for the principal hypotheses. Experiential EE was associated with higher skill-based and affective outcomes than traditional EE, but only in Estonia. The analysis indicated that the experiential form of intervention does not necessarily lead to higher levels of learning outcomes – in some cases even being associated with adverse effects; and that other factors (e.g. prior entrepreneurial aspirations, attitudes to educators) exhibit a significant influence on these outcomes. Affective outcomes acted as a consistent predictor of graduate employability, private early-stage EA as well as increasing the propensity of graduates to engage into nascent intrapreneurship. However, none of the objective outcomes showed the hypothesized dependency upon cognitive and skill-based learning outcomes. As far as the objective expressions of entrepreneurial behaviour were concerned in the period of the study, it did not matter significantly whether entrepreneurship was studied traditionally or experientially in Estonia, and the attendance of more experiential EE even tended to be less beneficial in Latvia. These results were largely divergent from conventional wisdom within human capital theory implying that investments in entrepreneurship-related human capital assets do not quite meet the expectations in the given context. The discussion of the results advances our understanding of why experiential EE might not work as expected. The findings are appraised from the viewpoint of entrepreneurship pedagogy, external factors affecting the development of local EE as well as other dimensions pertaining to EE design, delivery and the transfer of learning in the two countries. In particular, I find pertinent the intervention volume, the pedagogical and entrepreneurial experience of educators, the learning habits of students, coherence among teaching aims, methods used and outcomes expected as well as government support, and the availability of EE infrastructure, among other contextual influences. The dissertation concludes with recommendations for educators and decision-makers at HEIs, prospective students, policy makers in charge as well as EE scholars. Overall, this work contributes to topical debates in EE research with novel theoretical, methodological and empirical results.